Pre-clinical elective poster presentation and innovation day 2024 - Shaari, Syahrul Azlin Shaari; Kamal, Fatmawati (Faculty of Medicine, 2024)
Pre-clinical Elective Program is an annual activity of four weeks' duration.The participation comes from year 2 MBBS students who have satisfactorily passed their Pre-Clinical Professional Examination. At the end of the program, a poster day is held during the fourth week. This year was no exception, as it was successfully conducted on 29th August 2024 at the Faculty of Medicine UiTM, Sungai Buloh campus.